AI-Driven CRM: Integration of Cloud Architecture and Intelligent Automation in Enterprise Customer Management - Pradeep Kiran Veeravalli, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of artificial intelligence on Customer Relationship Management (CRM) systems through the integration of cloud architecture, system integration, and process automation capabilities. It explores how cloud-based CRM platforms provide scalable infrastructure supporting advanced functionality while eliminating traditional deployment barriers. The discussion addresses critical integration challenges and methodologies, creating unified customer data ecosystems across enterprise applications. Particular attention is given to AI applications, including natural language processing for conversational interfaces, machine learning algorithms for lead scoring, and predictive analytics for customer behavior modeling. The article presents implementation frameworks balancing automation efficiency with appropriate human intervention points, highlighting organizational considerations beyond technical requirements. Case examples illustrate successful deployments across industries, including healthcare, financial services, and manufacturing, demonstrating business impact through enhanced customer experiences and operational efficiencies. Governance frameworks ensuring ethical AI implementation and data quality maintenance are examined alongside future development directions. In addition to identifying ongoing learning opportunities in this quickly developing field, the thorough investigation offers practitioners implementation advice.
Keywords: AI-Driven CRM; Cloud Architecture; System Integration; Predictive Analytics; Customer Journey Orchestration